PENGEMBANGAN BAHAN AJAR E-MODUL MULTIMEDIA BERBASIS FLIP PDF CORPORATE MATERI REVOLUSI NASIONAL DI MALANG (1945-1949) UNTUK PEMBELAJARAN SEJARAH PESERTA DIDIK KELAS XI SMA PANJURA MALANG - Saadah, Alimatul (Universitas Negeri Malang, 2025)
The development of multimedia e-module teaching materials based on flip PDF-corporate material on the National Revolution in Malang 1945-1949 for history learning class XI students at SMA Panjura Malang was based on potential findings and existing problems. The research method used is research and development (RnD) by Sugiyono which consists of 10 stages, namely: 1) potential and problems, 2) data collection, 3) product design, 4) design validation, 5) design revision, 6) initial trials, 7) product revision, 8) use trials, 9) product revision, and 10) mass production. The results of this research and development are multimedia e-module teaching materials based on flip PDF-corporate materials on the National Revolution in Malang 1945-1949 which obtained material suitability validation test scores of 96%, teaching material suitability validation test scores of 86%, and product trials carried out by expert practitioners or teachers got a score of 96%, small group trials with 6 students in class XI-IPS 3 got a score of 85%, while large group trials with 14 students in class XI-IPS 3 obtained a score of 87%. Showing an increase of 2%, meaning that this teaching material is very valid and suitable for use in history learning in all class XI SMA Panjura Malang also answers based on the potential and problems found.